An overview of the role of health cadres in the early detection of non-communicable diseases - Hany, Alfrina; Putra, Kuswantoro Rusca; Wibisono, Ahmad Hasyim; Vatmasari, Ratih Arum; Syadilla, Iryne Putri; Anwar, Mochamad Saiful; Nurdiana, Sevia (Caring: Jurnal Pengabdian Masyarakat, 2025)
Non-communicable diseases (NCDs) are a growing global health problem and a leading cause of death. Health cadres play an important role in the detection and management of NCDs through health monitoring and community education. This community service aims to describe the role of health cadres in early detection of NCDs in the working area of Puskesmas Malang District. The training consisted of three main sessions, namely material on anthropometric measurements, the use of tensimeters and glucometers, and training in filling out NCD questionnaires commonly used in community health monitoring. This activity not only focuses on theory but also provides opportunities for participants to practice directly after the presentation session. Although most cadres have attended training, the application of skills in the use of medical devices and education related to NCDs is still limited. Continuous training and education is needed so that health cadres can optimise early detection and management of NCDs in the community.